2015
DOI: 10.3171/2015.3.focus1541
|View full text |Cite
|
Sign up to set email alerts
|

Anterior nuclear deep brain stimulation guided by concordant hippocampal recording

Abstract: OBJECT Anterior nuclear (AN) stimulation has been reported to reduce the frequency of seizures, in some cases dramatically; however, it has not been approved by the US Food and Drug Administration. The anterior nucleus is difficult to target because of its sequestered location, partially surrounded by the ventricle. It has traditionally been targeted by using transventricular or lateral transcortical routes. Here, the authors report a novel approach to targeting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…Interestingly, this hypothesis is supported by recent report using posterior trajectory to ANT together with hippocampal DBS capable of registering of evoked potentials [22]. They implanted electrodes along the posterior -anterior axis of ANT and found that only the most anterior contacts within ANT caused hippocampal evoked potentials while more posterior contacts did not.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, this hypothesis is supported by recent report using posterior trajectory to ANT together with hippocampal DBS capable of registering of evoked potentials [22]. They implanted electrodes along the posterior -anterior axis of ANT and found that only the most anterior contacts within ANT caused hippocampal evoked potentials while more posterior contacts did not.…”
Section: Discussionmentioning
confidence: 78%
“…There appears to now be a greater pace of development in lead and IPG technology in DBS, compared with VNS (a mature technology), which may affect costs in the future. Examples are rechargeable IPGs (25-year battery life), closed loop-stimulation (fewer side effects, greater battery life) and directional lead (current steering technology, which may result in better results from suboptimally placed leads, fewer revisions and fewer side effects) 38 39…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ventricular involvement in the trajectory is associated with significant targeting errors and an increased requirement for multiple brain passes in DBS [21]. Although paraventricular [13] and posterior inferior [22] approaches may minimize the risk of intraventricular bleeding in a transventricular trajectory, we think that these cannot incorporate the MD, situated posterior and inferior to the ANT, which is intimately involved in the maintenance and propagation of limbic epilepsies [1,23]. Furthermore, the long-term outcome and location of the electrodes have not been systematically investigated.…”
Section: Discussionmentioning
confidence: 99%